Physical Activity Indicators, Metabolic Biomarkers, and Comorbidity in Type 2 Diabetes. Issue 4 (2nd October 2019) - Akinci, Buket; Yeldan, Ipek; Celik, Selda; Satman, Ilhan
ABSTRACT: Purpose: This study aimed (1) to compare physical activity (PA) indicators, metabolic biomarkers, and comorbidity, (2) to investigate the relationship between PA indicators and metabolic biomarkers, comorbidity and (3) to identify barriers to PA in patients with type 2 diabetes (T2DM) who are using oral hypoglycaemic agent (OHA) or combined OHA and insulin (OHAiN). Methods: Sixty-one patients were classified as patients using only OHA or combined OHAiN. Metabolic biomarkers (waist-to-hip ratio, body mass index (BMI), lipid profile, glycosylated haemoglobin (HbA1c), fasting blood glucose, comorbidity and PA indicators (self-reported PA, number of steps (NOS), 6-minute walking distance (6MWD)) were assessed. PA perceptions and reasons for inactivity were questioned. Results: The comorbidity ( p = .013), low-density lipoprotein-cholesterol ( p = .026), total cholesterol ( p = .008) and HbA1c ( p = .020) were higher and PA level was lower ( p = .007) in the OHAiN group. NOS was positively correlated with high-density lipoprotein-cholesterol ( p = .037) and negatively correlated with BMI ( p = .007). 6MWD was negatively correlated with BMI ( p = .014) and comorbidity ( p = .004) in the OHA group. BMI was a significant predictor of NOS (adjusted R 2  = 0.242) and comorbidity for 6MWD (adjusted R 2  = 0.250) in the OHA group. The majority of the patients (OHA = 34.3%, OHAiN = 42.3%) reported "lack of time" as the most common barrier to PA. Conclusions: This study showed that patients on OHAiN have lower PA levels, poorer metabolic profiles, and higher comorbidity rates than OHA users. PA indicators were related with some metabolic biomarkers and comorbidity in only OHA users. The most common reason for inactivity was "the lack of time" in both groups.